Adenovirus Encoding Tumor Necrosis Factor Alpha and Interleukin 2 Induces a Tertiary Lymphoid Structure Signature in Immune Checkpoint Inhibitor Refractory Head and Neck Cancer - Clubb, James H. A.; Kudling, Tatiana V.; Heiniö, Camilla; Basnet, Saru; Pakola, Santeri; Cervera Carrascón, Víctor; Santos, João Manuel; Quixabeira, Dafne C. A.; Havunen, Riikka; Sorsa, Suvi; Zheng, Vincent; Salo, Tuula; et al. (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors (ICI) have provided significant improvement in clinical outcomes for some patients with solid tumors. However, for patients with head and neck cancer, the response rate to ICI monotherapy remains low, leading to the exploration of combinatorial treatment strategies. In this preclinical study, we use an oncolytic adenovirus (Ad5/3) encoding hTNFα and hIL-2 and non-replicate adenoviruses (Ad5) encoding mTNFα and mIL-2 with ICI to achieve superior tumor growth control and improved survival outcomes. The in vitro effect of Ad5/3-E2F-D24-hTNFa-IRES-hIL-2 was characterized through analyses of virus replication, transgene expression and lytic activity using head and neck cancer patient derived cell lines. Mouse models of ICI naïve and refractory oral cavity squamous cell carcinoma were established to evaluate the local and systemic anti-tumor immune response upon ICI treatment with or without the non-replicative adenovirus encoding mTNFα and mIL-2. We delineated the mechanism of action by measuring the metabolic activity and effector function of CD3+ tumor infiltrating lymphocytes (TIL) and transcriptomic profile of the CD45+ tumor immune compartment. Ad5/3-E2F-D24-hTNFa-IRES-hIL-2 demonstrated robust replicative capability in vitro across all head and neck cell lines screened through potent lytic activity, E1a and transgene expression. In vivo, in both ICI naïve and refractory models, we observed improvement to tumor growth control and long-term survival when combining anti-PD-1 or anti-PD-L1 with the non-replicative adenovirus encoding mTNFα and mIL-2 compared to monotherapies. This observation was verified by striking CD3+ TIL derived mGranzyme b and interferon gamma production complemented by increased T cell bioenergetics. Notably, interrogation of the tumor immune transcriptome revealed the upregulation of a gene signature distinctive of tertiary lymphoid structure formation upon treatment of murine anti-PD-L1 refractory tumors with non-replicative adenovirus encoding mTNFα and mIL-2. In addition, we detected an increase in anti-tumor antibody production and expansion of the memory T cell compartment in the secondary lymphoid organs. In summary, a non-replicative adenovirus encoding mTNFα and mIL-2 potentiates ICI therapy, demonstrated by improved tumor growth control and survival in head and neck tumor-bearing mice. Moreover, the data reveals a potential approach for inducing tertiary lymphoid structure formation. Altogether our results support the clinical potential of combining this adenovirotherapy with anti-PD-1 or anti-PD-L1.